Impact and Dynamics of Stakeholders in Indonesia through the Public Service Evaluation Revolution - Prasetyo , Rizki Aninditya; UB, Ahmad Riyadh (Indonesian Journal of Public Policy Review, 2024)
This qualitative descriptive study investigates the implementation of PermenPAN RB No. 6 of 2022 on civil service performance assessment at BKD Sidoarjo, Indonesia. Using interviews, observation, and documentation, the research explores how the policy provides subjective assessments, tracks employee work for personal and organizational evaluation, and involves stakeholders in the assessment process. Findings indicate that the policy aligns with stakeholder expectations, facilitates dialogue between employees and superiors, and employs various strategies for performance evaluation. This study contributes to understanding policy implementation dynamics in public administration, emphasizing the importance of aligning policy objectives with practical strategies to improve employee competency and organizational effectiveness in the public sector. Highlights: Examines PermenPAN RB No. 6's implementation, effectiveness in civil service assessment. Emphasizes stakeholder involvement, vital for policy alignment and organizational goals. Highlights need for practical strategies, enhancing employee competency in public administration. Keywords: Policy Implementation, Civil Service Performance Assessment, Stakeholder Involvement, Public Administration, Organizational Effectiveness